2018
DOI: 10.1016/j.ijnurstu.2018.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Leadership styles and outcome patterns for the nursing workforce and work environment: A systematic review

Abstract: The findings of this systematic review provide strong support for the employment of relational leadership styles to promote positive nursing workforce outcomes and related organizational outcomes. Leadership focused solely on task completion is insufficient to achieve optimum outcomes for the nursing workforce. Relational leadership practices need to be encouraged and supported by individuals and organizations to enhance nursing job satisfaction, retention, work environment factors and individual productivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
504
0
26

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 430 publications
(578 citation statements)
references
References 314 publications
16
504
0
26
Order By: Relevance
“…As has been reported in previous studies, we found that emotionally intelligent leadership practices by formal nursing leaders had a direct relationship with staff job satisfaction. The link between emotionally intelligent leadership and job satisfaction has been reported in multiple empirical studies and research reviews (Cowden, Cummings, & Profetto‐McGrath, ; Cummings, Hayduk, & Estabrooks, ; Cummings, MacGregor, et al., ). Resonant leadership significantly predicted manager support which in turn predicted coaching conversations.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…As has been reported in previous studies, we found that emotionally intelligent leadership practices by formal nursing leaders had a direct relationship with staff job satisfaction. The link between emotionally intelligent leadership and job satisfaction has been reported in multiple empirical studies and research reviews (Cowden, Cummings, & Profetto‐McGrath, ; Cummings, Hayduk, & Estabrooks, ; Cummings, MacGregor, et al., ). Resonant leadership significantly predicted manager support which in turn predicted coaching conversations.…”
Section: Discussionmentioning
confidence: 90%
“…Difficulties recruiting and retaining nursing staff make it challenging for nursing homes to meet recommended standards for nursing and personal care staffing (e.g., 3.5 hours per resident per day; Chu, Wodchis, & McGilton, ). Nurse leaders, particularly those who are relationally focused, play an important role in staff job satisfaction, nurse empowerment, staff retention (Cummings, MacGregor, et al., ), patient and resident satisfaction (Wong, Cummings, & Ducharme, ), productivity (Cummings, MacGregor, et al., ), and in improving patient outcomes (Wong et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Fiedler argued that relation‐focused management is best suited in work situations with moderate uncertainty and moderate structure which is characteristic of eldercare work, and a review of management practices within nursing by Cummings et al showed that relationship‐focused leadership styles were related to greater job satisfaction, better work environment and better work outcomes within nursing than other leadership styles. According to Cummings et al , it may be that managers who focus primarily on the task to be completed do not pay due attention to developing and maintaining relationships with staff members. In contrast, managers who are relationally focused are building trust by listening, being empathetic and responding to employee concerns .…”
Section: Discussionmentioning
confidence: 99%
“…Challenges include inadequate preparation and support to undertake the leadership role, role ambiguity, increased span of control and increased administrative load reducing opportunities for NUMs to be clinical leaders (Gunawan et al, 2018). Significantly, role stress for NUMs potentially threatens their work-life balance, decision-making, quality of care and turnover intent (Steege et al, 2017;Udod et al, 2017); the recruitment and retention of NUMs (Brown et al, 2013;Hewko, Brown, Fraser, Wong, & Cummings, 2015;Lee & Cummings, 2008;Loveridge, 2017;Shirey et al, 2010); the creation of positive safety climate and work environment (Simpson et al, 2017); and the satisfaction and retention of staff (Cummings et al, 2018;Duffield, Roche, Blay, & Stasa, 2010; Morsiani, Bagnasco, & Sasso, 2017; Saleh et al, 2018).…”
Section: Backg Rou N Dmentioning
confidence: 99%